Thermodynamic process and performance of high n-butanol/gasoline blends fired in a GDI production engine running wide-open throttle (WOT). (15th November 2017) - Chen, Zheng; Zhang, Yanqun; Wei, Xiaotai; Zhang, Quanchang; Wu, Zhenkuo; Liu, Jingping
Highlights: 30% and 50% n -butanol were added into a GDI engine running WOT. Max BMEP increased to 1.99 MPa with 50% n -butanol blend. High n -butanol/gasoline blends can promote combustion. High n -butanol/gasoline blends decreases exhaust temperature. High n -butanol/gasoline blends reduces NOx and CO2 . Abstract: A turbocharged Gasoline Direct Injection (GDI) engine fueled by n -butanol/gasoline blends is studied under the condition of wide-open throttle (WOT) in this paper. The effects of high n -butanol content (30% and 50% n -butanol by volume, i.e. Bu30 and Bu50) on the thermodynamic process and fuel efficiency of the GDI engine are discussed, as well as the engine emissions. Also, the results are compared with RON 93 gasoline and 10% ethanol/gasoline blended fuel (E10), which have been widely used in cars. The results show that high content of butanol addition can be realized in the GDI engine without any modification to its structure and control. Moreover, the maximum BMEP of the engine can increase to 1.99 MPa with Bu50. As compared with the gasoline and E10, high n -butanol/gasoline blends increase in-cylinder combustion pressure and pressure rise rate, promote ignition, and shorten burning duration. What is more, high n -butanol/gasoline blends improve combustion stability and decrease exhaust temperature, but they cannot deteriorate anti-knock quality. However, high n -butanol/gasoline blends increase Brake Specific Fuel Consumption (BSFC), and they decrease combustion efficiency and Brake Thermal Efficiency (BTE) at WOT. As for the engine emissions, high n -butanol/gasoline blends increase UHC and CO emissions but reduce NOx and CO2 emissions. The study implies that 0–50% butanol/gasoline blends can directly replace the existing engines fueled with regular RON 93 gasoline or E10.